The Influence of Debt to Asset Ratio and Working Capital Turnover on Profit Growth at PT Betonjaya Manunggal Tbk in the 2012-2023 Period - Zahroh, Ainun Nur Fatma Anisaatul; Lubis, Iman (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2024)
The research aims to determine the effect of Debt To Asset and Working Capital Turnover on Profit Growth at PT Betonjaya Manunggal Tbk for the 2012-2023 period. The population used in this research is the financial report of PT Betonjaya Manunggal Tbk and the sample from this research is the balance sheet and profit and loss report of PT Betonjaya Manunggal Tbk for the 2012-2023 period. Data analysis techniques use the classical assumption test, simple regression analysis, multiple regression analysis, coefficient of determination analysis test, hypothesis testing using the t-test and f-test and f-test. Partial test results show that Debt to Asset Ratio (DAR) has no significant effect on Profit Growth, Working Capital Turnover (WCT) has a significant effect on Profit Growth. Meanwhile, the results of simultaneous testing of Debt to Asset Ratio (DAR) and Working Capital Turnover (WCT) do not simultaneously influence Profit Growth.